Components of Market Orientation in Frozen Food Business - Distanont, Anyanitha (WMS Journal of Management, 2018)
This research is aimed to study the market orientation which is a basic leading to innovation in the frozen food business in the context of small and medium-sized enterprise (SME). The research process consists of six stages: 1) the review of the literature and relevant studies, 2) development of the research model, 3) development of data collection tool, 4) the conduction of empirical research where the data collected from the questionnaires, 5) the analysis of research data by using statistical technique; namely, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), and 6) research conclusion. The population of this study is the frozen food business which is registered as SMEs under the office of small and medium enterprise promotion. The sample size is 410. The findings found that the component of market orientation affecting innovation can be classified into four dimensions six components as 1) customer: need and customer feedback, 2) supplier, 3) industry: competitor pressure and industry information sharing , and 4) national and international context: government support and regulation. The findings indicate the importance of market orientation as an external element that will be foundation for creating innovation in the future. SMEs can adapt and gradually develop and lead to sustainable long-term competitiveness.